Combinational Antibacterial Activity of Nisin and 3-Phenyllactic Acid and Their Co-production by Engineered Lactococcus lactis - Liu, Jiaheng; Huang, Rongrong; Song, Qianqian; Xiong, Hui; Ma, Juan; Xia, Rui; Qiao, Jianjun (Frontiers in Bioengineering and Biotechnology, 2021)
Nisin produced by certain Lactococcus lactis strains is commercially used in meat and dairy industries because of its effective antibacterial activity and food safety characteristics. It has been proved that nisin had synergetic activity with other antimicrobial agents. In this study, we demonstrated that nisin and phenyllactic acid (PLA) in combination displayed excellent synergistic antibacterial activity against foodborne pathogens including S. xylosus and M. luteus. The potential application in food preservation was further verified via microbial analysis during the storage of meat and milk, and determination of strawberry rot rate. Scanning electron microscopy observation indicated a distinct mode of PLA with nisin, which may target at the dividing cell, contributing to their synergistic effect. Considering the positive results, a nisin-PLA co-producing strain was constructed based on the food-grade strain L. lactis F44, a nisin Z producer. By the knockout of two L-lactate dehydrogenase (LDH) and overexpression of D-LDHY25A, the yield of PLA was significantly increased 1.77-fold in comparison with the wild type. Anti-bacterial assays demonstrated that the fermentation product of the recombinant strain performed highly effective antibacterial activity. These results provided a promising prospect for the nisin-PLA co-expressing L. lactis in food preservation on account of its considerable antibacterial activity and cost-effective performance.